Language and art activities at primary level: the EE dimension - B Holderness; N.W. Motlhala; R McCallum (Environmental Association of Southern Africa, 1986)
The inter-relationship of language and art with environmental education (EE) within the Primary Education Upgrading Prograrnne (PEUP) in Bophuthatswana is described and discussed.